2021
DOI: 10.1111/aor.14142
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation seems to induce impairment of primary hemostasis pathology as measured by a Multiplate analyzer: An observational retrospective study

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) support is often associated with bleeding complications caused by secondary or primary hemostasis pathology. However, there are limited data investigating primary hemostasis using Multiplate aggregometry with specific diagnostics tests for vWF (von Willebrand factor) deficiency. Aims:The aim of this study was to find out whether short-term ECMO produces the pathology of primary hemostasis that is detected by Multiplate aggregometry and to investigate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, having a more significant number of investigated subjects would be advisable, which would add even more weight to the entire study. Similarly, a particular bias may have been introduced into this study because the primary hemostasis disorder was not investigated; primary hemostasis can be disturbed as part of ECMO support during lung thereby potentiating intraoperative bleeding [22]. The authors hypothesize that the significantly higher incidence of PGD grade 3 in 72 h postop in the group with higher doses of UFH may be caused by the need to administer a larger number of blood derivatives, which is one of the possible reason for the development of PGD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, having a more significant number of investigated subjects would be advisable, which would add even more weight to the entire study. Similarly, a particular bias may have been introduced into this study because the primary hemostasis disorder was not investigated; primary hemostasis can be disturbed as part of ECMO support during lung thereby potentiating intraoperative bleeding [22]. The authors hypothesize that the significantly higher incidence of PGD grade 3 in 72 h postop in the group with higher doses of UFH may be caused by the need to administer a larger number of blood derivatives, which is one of the possible reason for the development of PGD.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mabel Chung et al analysed V-A ECMO patients from the Extracorporeal Life Support Organization registry and found that 44.1% of those patients suffered some kind of hemocompatibility-related adverse events (62.1% bleeding, 37.9% thrombotic events and the crude in-hospital mortality rate was 58.6%) [6]. We recently published two studies describing primary haemostasis pathology found in patients on ECMO support that was detected by PFA 200 analysers and Multiplate aggregometry [3,4], and we showed that this phenomenon can be used together with LMWH as an alternative way of ECMO and patient anticoagulation [3]. We use this combination routinely, and this case supports our previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, ECMO machines produce complex coagulopathy that consists of a pathology of secondary haemostasis (fibrinolysis, coagulation factor deficiency, thrombocytopenia, heparin overdose) as well as primary haemostasis pathology (acquired von Willebrand syndrome, acquired platelet dysfunction) [ 2 ]. We have recently published two studies describing primary haemostasis pathology found in patients on ECMO support as detected by a PFA 200 analyser and Multiplate aggregometry [ 3 , 4 ], and we showed that together with low molecular weight heparin (LMWH), this combination may prevent ECMO devices and the patients themselves from clotting [ 3 ]. This paper presents the case of a patient who spent 94 days on ECMO without life threatening bleeding or thrombotic complications.…”
Section: Introductionmentioning
confidence: 99%